Incorporating online teaching in an introductory pharmaceutical practice course: a study of student perceptions within an Australian University. - Benino, Diana; Girardi, A.; Czarniak, Petra (Centro de Investigaciones y Publicaciones Farmaceuticas, 2011)
To examine student perceptions regarding online lectures and quizzes undertaken during a pharmaceutical practice course for first year undergraduate students enrolled in the Bachelor of Pharmacy course at an Australian University. Methods: The University uses a standard instrument to collect feedback from students regarding unit satisfaction. Data were collected for three different teaching modalities: traditional face-to-face, online and partially online. Results: Descriptive statistics support that, from a student's perspective, partial online delivery is the preferred teaching methodology for an introductory pharmaceutical practice unit. Conclusion: This study has served to highlight that while there are a few points of significant difference between traditional and online teaching and learning, a combination of the two provides a reasonable avenue for teaching exploration. This result has implications for teaching practice generally, and within the pharmacy discipline, specifically.